Nahw Dalam Perspektif Ibn Madhā Dan Syauqi Dhaīf - Kasmantoni Kasmantoni (Institut Agama Islam Negeri Bengkulu, 2014)
This paper aims to explain that; what Ibn Madha is merely an attempt to restore nahw the first purpose, namely as a tool for studying garamtikal in Arabic. Therefore, whatever the reason put forward Ibn Madha is not really necessary. The important thing is whether the concept was no point in learning Arabic or not. Or maybe even the opposite can menyulitakn to be deepened. It's just business Ibn Madha is still at the theoretical level, it is necessary for practical efforts in order to realize these suggestions. One responds to the suggestions is Syauqy are doubtful that takes ideas Nahw epistemological reasoning as the basis. Although there are differences here and there, but the difference, not the basic principles of syntax. However Nahw an effort to simplify the effort still needs to be developed in view of the scarcity of such research results especially in the context of the application.